Integrating Structural-Functional Theory with KAP Analysis: Understanding HIV Transmission Risk in Nepal - Paudel, Nikita; Mariam, Alesh (NPRC Journal of Multidisciplinary Research, 2026)
Background: Nepal continues to be exposed to HIV transmission risks despite several decades of public health initiatives, especially within the Kathmandu Valley, where internal migration, workforce mobility, and other structural factors combine. Despite this persistent gap between HIV KAP, individual-level behavior models offer an insufficient explanation of the problem. Objective: The current systematic review seeks to use structural-functional theory to supplement empirical findings on KAP to understand the dynamics of HIV transmission risks in Nepal, as well as identify patterns of publications, citations, authorship, and country/organizational productivity for the last ten years. Methods: A systematic search was performed through Dimension.ai using Boolean terms: ("HIV" OR "AIDS" OR "HIV transmission") AND ("KAP" OR "knowledge attitude" OR "knowledge practice") AND ("Nepal" OR "Kathmandu Valley"). A total of 107 articles have been identified as published in the period between 1st January 2017 and 10th April 2026. Bibliometrics was performed through VOSviewer with regard to authorship network analysis, citations, and word clouds. Findings: The research production is largely clustered in Health Sciences (71), Biomedical and Clinical Sciences (66), and Human Society (64). The publishing trend demonstrates some growth up to ten publications in 2024 before drastically falling off. Citations increased steadily from 71 (2017) until reaching their maximum of 147 (2024) before significantly reducing to 27 in 2026. Nepal is prominent in documents (43) and citations (475), accompanied by high collaboration with Japan (299 citations), the United Kingdom (223 citations), and the United States (214 citations). Tribhuvan University (12 documents, 213 citations) and the University of Tokyo (9 documents, 299 citations) serve as the core institutions. "HIV," "knowledge," "health," "practice," and "Nepal" emerge as key topics based on word cloud analysis. Conclusion: The combination of structural-functional theory and KAP analysis shows that HIV transmission risk in Nepal results from the interaction between systemic dysfunctions such as cultural taboo, economic weakness, and institutional gaps with individual-level KAP disjunctions. Future research should diversify methodological approaches, consider rural areas, and focus on intervention-related studies for consistent behavior modification.